Das Johannesevangelium und der Magische Realismus. Eine Studie zu den magisch-realistischen Zügen des vierten Evangeliums, im Vergleich mit Cien años de soledad (Gabriel García Márquez) - Hund Carrasco, Alois Alexander (Universitätsbibliothek der Johannes Gutenberg-Universität Mainz, 2024)
Many scenes in the Gospel of John go beyond the limits of the imaginable, giving the impression that their content belongs to the realm of fantasy. The author, however, guarantees that the narrative – including events alien to reality – is based on historical events. In this way, John triggers a conflict on the meta-level of perception: The reader is invited to consider impossible events as possible ones. The Johannine depiction of the life of Jesus fuses unreal scenes with a realistic narrative context in a form that reminds one of the narratives of Magical Realism that emerged in the 20th century. Because of its magical realist features, the Gospel of John could be considered a precursor of the genre. Based on this thesis, the present study aims to gain new approaches to explore the literary miraculous in the Gospel of John from new angles through a dialogue between theology and literary studies.